USING DOUBLE ENTRY JOURNALS TO IMPROVE READING COMPREHENSION AND DESCRIPTIVE WRITING ACHIEVEMENTS - DIAN KHAIRANI; ISMAIL PETRUS; DINAR SITINJAK (Sriwijaya University Learning and Education International Conference, 2016)
This research aimed at investigating whether or not there were significantdifferences in reading and writing achievements between the eighth graders whowere taught by using Double Entry Journals and those who were not. Sixty studentswere purposively chosen as the subjects and divided into experimental (N= 30) andcontrol groups (N= 30). The data were collected by means of tests and questionnaireand statistical analysis. The results showed that the t-value of the students’ readingcomprehension achievement in the experimental group was 11.575, and the t-valuebetween the two groups was 5.982. Meanwhile, the t-value for writing achievementin the experimental group was 4.429, and the t-value between the two groups was1.345. The contributions of each aspect of reading comprehension and writing werealso presented. The results indicated that Double Entry Journals were mostlyeffective for improving reading comprehension achievement but were not effectivefor writing.